A Novel Incentive-Compatible Neural Network Optimization Model (ICNNOM) with Optimal Contract Structure - Zhang, Jincheng; Zhang, Jindong (Peneliti Teknologi Teknik Indonesia, 2025)
In this paper, we propose a novel neural network optimization framework called the Incentive Compatible Neural Network Optimization Model (ICNNOM). This model combines the incentive compatibility idea in game theory with the optimal contract theory to simulate the